Comparison of Suprachoroidal Triamcinolone Injection and Modified Grid Laser in Treatment of Refractory Diabetic Macular Edema: Comparison of Suprachoroidal Triamcinolone Injection and Modified Grid Laser - Aleem, Nouman; Ahmad, Muhammad Abrar; Ain, Noor ul; Rehman, Tayyab; Usman Akhtar, Hafiz Muhammad; Rashid, Faisal (Pakistan Journal of Health Sciences, 2024)
Diabetic macular edema is the leading cause of blindness in diabetic eye disease. The most important cause of visual impairment is diabetes-induced macular edema also called DME which involves central part of the macula lutea. Objective: To compare the outcome of suprachoroidal triamcinolone injection and modified grid laser in the treatment of refractory diabetic macular edema. Methods: This prospective cohort study was done for 12 months (January 2021 to December 2021) on 56 patients having refractory diabetic macular edema. The technique of non-probability consecutive sampling was used. Patients in Group A received a suprachoroidal injection of 4 mg triamcinolone. Patients in Group B underwent modified grid photocoagulation. After 4 months of treatment, the patients' visual acuity and central macular thickness were assessed again using Snellen's chart and Optical Coherence Tomography (OCT) respectively. Results: After 4 months, the mean BCVA in Group-A was 0.57 + 0.127 and in Group-B was 0.83 + 0.150 (P=0.000) while the mean improvement (change line) was 1.6 + 0.318 and 0.89 + 0.229 (P=0.001), respectively In Group-A, improvement in Central Macular Thickness (CMT) was observed in 24 (85.7%) patients, while in Group-B, improvement in Central Macular Thickness was seen in 17 (60.7%) patients. After 4 months, the mean CMT in Group-A was 302.68 + 14.427 um and in Group-B was 339.71 + 54.821 um (P=0.009) while the mean improvement (change) was 153.89 + 30.902 um and 95.57 + 41.111 um (P=0.024), respectively. Conclusion: Suprachoroidal triamcinolone injection was found to be more effective than modified grid laser in treatment of DME.